The Landscape of Condyloma Acuminata and Concomitant STIs in Denpasar: A Retrospective Analysis with Implications for Public Health Strategies - Ni Putu Wina Widyastuti; Ni Made Dwi Puspawati; I Gusti Ayu Agung Elis Indira; Aditya Permana (HM Publisher, 2025)
Background: Condylomata acuminata (CA) is a prevalent sexually transmitted infection (STI). Research into the risk factors and characteristics associated with CA is crucial for developing effective prevention strategies. This study aimed to determine the prevalence and characteristics of CA patients at Prof. Dr. I.G.N.G. Ngoerah General Hospital in Denpasar, Bali, Indonesia. Methods: A retrospective cross-sectional study was conducted using medical records of CA patients attending the STI and Dermatology Clinic at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, from January 2021 to December 2023. Data collected included patient visit status, age, gender, occupation, education, concomitant STIs, sexual orientation, marital status, and use of protective measures. Data were processed descriptively. Results: Of 284 CA patients, 69.7% were male and 30.3% were female. The mean age was 28.99 ± 11.38 years. Married individuals constituted 41.5% of cases. Private employees were the predominant occupation (34.2%). Fifty percent of patients had no concomitant STIs, while HIV was present in 37.7% of the total sample (75.4% of those with any concomitant STI). A significant proportion (49%) reported not using protective measures during sexual intercourse. Conclusion: The prevalence of CA at Prof. Dr. I.G.N.G. Ngoerah General Hospital, Denpasar, was 40 per 1000 visits during the study period. CA was predominantly observed in adult males who were married, heterosexual, had completed high school, worked as private employees, and did not use protective measures during sexual intercourse. These findings underscore the need for targeted public health interventions.